Heat-killed cell preparation of Corynebacterium glutamicum stimulates the immune activity and improves survival of mice against enterohemorrhagic Escherichia coli. Issue 5 (4th May 2017) - Ebisawa, Makoto; Tsukahara, Takamitsu; Fudou, Ryosuke; Ohta, Yasuhiro; Tokura, Mitsunori; Onishi, Norimasa; Fujieda, Takeshi
Abstract: Fermentation by Corynebacterium glutamicum is used by various industries to produce L-Glutamate, and the heat-killed cell preparation of this bacterium (HCCG) is a by-product of the fermentation process. In present study, we evaluated the immunostimulating and survival effects against enterohemorrhagic Escherichia coli (STEC) infection of HCCG. HCCG significantly stimulated in vitro IgA and interleukin-12 p70 production in murine Peyer's patch cells and peritoneal macrophages, respectively. Oral administration of 10 mg/kg body weight (BW) of HCCG for seven consecutive days stimulated IgA concentration in murine cecal digesta. Mice were orally administered HCCG for 17 consecutive days (d0–d17), and challenged with STEC on d4 to d6. Survival of mice tended to improve by 100 mg/kg BW of HCCG administration compared with those in control group. In conclusion, HCCG supplementation was found to prevent STEC infection in mice, and thus it may have the potential to stimulate the immune status of mammals. Graphical abstract: : Cell wall preparation of Corynebacterium glutamicum prevented of pathogenic E.coli infection through enhancement of immune function such as IgA secretion in the intestine.